Health impacts and functional properties of lycopenes: A Review - Ali Motamedzadegan; Azita Nemati (Journal of Food and Bioprocess Engineering, 2022)
There is now a growing awareness of a healthy lifestyle in the community and people are looking for useful products in their diet. Functional foods are therefore of great importance to health. Lycopene is a carotenoid that causes the red color in fruits and vegetables. Lycopene is one of the most effective antioxidants among the carotenoids. Lycopene is synthesized by some plants and microorganisms and is the predominant carotenoid found in human serum, and as a pharmaceutical supplement, it protects important cell biomolecules - such as DNA, proteins and fats - from the oxidation and destruction of their radicals. It plays an important role in reducing the risk of cardiovascular diseases as well as treating metabolic syndrome, liver disease and cancers. In this article, the characteristics of lycopene and its effect on human health and treatment of diseases are reviewed.